Exploring Teachers’ Priorities in Teaching English Poetry: A Focus Area Analysis - Sharma, Lok Raj (Nepal Journal of Multidisciplinary Research, 2025)
Background: Teaching English poetry is a complex task that demands imaginative, creative, experienced, dedicated, and resourceful teachers. Effective poetry instruction helps students develop a sound evaluation, veritable appreciation, and balanced interpretation of poetic works. Understanding teachers’ priorities in teaching poetry can enhance pedagogical strategies and improve student engagement with literary texts. Objective: This study aims to explore the key focus areas prioritized by teachers while teaching English poetry in grades XI and XII. The research specifically examines instructional emphases in 20 academic institutions within Hetauda sub-metropolitan city, Nepal. Methods: A cross-sectional research survey design was employed. Primary data were collected through a structured questionnaire administered to 50 English teachers in 2024. The sample was drawn from a population of 57 using a simple random sampling technique with a 5% margin of error. Descriptive analysis was used to interpret the data. Additionally, secondary data from books and journal articles were reviewed to provide context and support the primary findings. Findings: The study identified key areas emphasized in teaching English poetry, including title, theme, speaker, tone, setting, diction, figurative language, sound devices, historical and cultural context, and form and structure. Among these, title, theme, and speaker were the most frequently prioritized aspects. Conversely, elements such as epigraph, motif, layout, punctuation, and epitaph were given minimal attention in poetry instruction. Conclusion: The findings suggest that teachers focus primarily on thematic and structural aspects of poetry, with less emphasis on certain literary and stylistic devices. This highlights potential gaps in poetry instruction and suggests the need for a more comprehensive teaching approach that incorporates overlooked poetic elements. Novelty: This study contributes to the pedagogical literature on English poetry education by systematically identifying and analyzing teachers' instructional priorities. It provides empirical insights into poetry teaching practices, offering valuable guidance for curriculum design and teacher training to enhance poetry appreciation and literary analysis skills among students.